THE SPIRITUAL GUIDE (guru) AND THE DISCIPLE (sisya) IN INDIAN TRADITION - Bilimoila, Purusottama (Journal of Dharma, 1980)
The term. guru has nowadays become a household word in the West, and almost anybody who pretends to speak with authorityWest, and almost anybody who pretends to speak with authority is called a guru. It is also a much misunderstood and abused term. But let me make it clear that I am. not speaking as a guru-rather I am speaking as a siya or disciple, a seeker invocation that a Hindu pupil chants out of love for his/her teacher.